Lysosomal enzyme trafficking factor LYSET enables nutritional usage of extracellular proteins - Pechincha, Catarina; Größl, Sven; Kalis, Robert; Almeida, Melanie de; Zanotti, Andrea; Wittmann, Marten; Schneider, Martin; Campos, Rafael P. de; Rieser, Sarah; Brandstetter, Marlene; Schleiffer, Alexander; Müller-Decker, Karin; et al. (Science, 2022)
Mammalian cells can generate amino acids through macropinocytosis and lysosomal breakdown of extracellular proteins, which is exploited by cancer cells to grow in nutrient-poor tumors. Through genetic screens in defined nutrient conditions, we characterized LYSET, a transmembrane protein (TMEM251) selectively required when cells consume extracellular proteins. LYSET was found to associate in the Golgi with GlcNAc-1-phosphotransferase, which targets catabolic enzymes to lysosomes through mannose-6-phosphate modification. Without LYSET, GlcNAc-1-phosphotransferase was unstable because of a hydrophilic transmembrane domain. Consequently, LYSET-deficient cells were depleted of lysosomal enzymes and impaired in turnover of macropinocytic and autophagic cargoes. Thus, LYSET represents a core component of the lysosomal enzyme trafficking pathway, underlies the pathomechanism for hereditary lysosomal storage disorders, and may represent a target to suppress metabolic adaptations in cancer.
Gesehen am 27.06.2023